2020
DOI: 10.6004/jnccn.2020.0017
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Guidelines Insights: Genetic/Familial High-Risk Assessment: Breast, Ovarian, and Pancreatic, Version 1.2020

Abstract: The NCCN Guidelines for Genetic/Familial High-Risk Assessment: Breast, Ovarian, and Pancreatic provide recommendations for genetic testing and counseling for hereditary cancer syndromes, and risk management recommendations for patients who are diagnosed with syndromes associated with an increased risk of these cancers. The NCCN panel meets at least annually to review comments, examine relevant new data, and reevaluate and update recommendations. These NCCN Guidelines Insights summarize the panel’s discussion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
448
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 386 publications
(458 citation statements)
references
References 89 publications
7
448
0
3
Order By: Relevance
“…PCPs apply familial risk assessment tools to women with a personal or family history of breast or ovarian/tubal/peritoneal cancers, or who have an ancestry indicative of BRCA1/2 gene mutations (2). This reliance on PCPs could provide a challenge considering that cancer risk models continuously evolving to include additional etiologic and genetic risk factors (1,40) and these updated models may not be effectively incorporated into primary care practices. Previous studies have shown that guideline dissemination is not necessarily adequate to change practice behavior (41,42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PCPs apply familial risk assessment tools to women with a personal or family history of breast or ovarian/tubal/peritoneal cancers, or who have an ancestry indicative of BRCA1/2 gene mutations (2). This reliance on PCPs could provide a challenge considering that cancer risk models continuously evolving to include additional etiologic and genetic risk factors (1,40) and these updated models may not be effectively incorporated into primary care practices. Previous studies have shown that guideline dissemination is not necessarily adequate to change practice behavior (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Risk assessment for breast and ovarian cancer include assessment of hereditary and demographic factors including age, family history, genetic testing results (self/relatives) and ancestry (1,2) (National Comprehensive Cancer Network Clinical Practice Guidelines in Oncology (NCCN Guidelines®), https://www.nccn.org/professionals/physician_gls/default.aspx). Breast cancer screening recommendations for women at average risk include mammography, although guidelines are inconsistent in terms of starting age and frequency (3-5) (Susan G. Komen Breast Cancer Screening for Women at Average Risk, https://ww5.komen.org/BreastCancer/BreastCancerScreeningforWomenatAverageRisk.html).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data analysis further indicates that 3 times the deaths resulting from colorectal cancer would be avoided with one third of current costs if colorectal cancer screening rates in people aged 50-70 years improved to 80% [ 15 ]. For the genetically predisposed individual, the benefit of prescribed cancer screening has an even greater impact [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multigene panel testing has revealed that germline loss-of-function mutations/pathogenic variants (PVs) in various cancer-associated genes are identified in more than 10% and 20% of patients with BC and OC, respectively [1][2][3]. Attempts have been made to define the genetic/familial risk of BC/OC associated with these genes, and subsequently, management recommendations for carriers of PVs in some of the high-penetrance genes have been established [4,5]. Despite this, several genes in which PVs confer low-or moderate-penetrance effects still require more evidence and more convincing assessments of BC/OC risk to utilize them in recommendations for carriers.…”
Section: Introductionmentioning
confidence: 99%